Føljetonromanen og dansk mysterie-litteratur i 1800-tallet - Lehrmann, Ulrik (Passage - Tidsskrift for litteratur og kritik, 2018)
Eugène Sue’s Les Mystères de Paris (The Mysteries of Paris; published in a newspaper from 1842 to 1843) holds a central position among the serial novels in the 19th century. The dominant legitimate literary culture regarded Sue and the French serial literature as bad and unhealthy taste, but nevertheless all over Europe Les Mystères de Paris was read and adapted in local versions. This format exchange is an early example of the transnational reach of popular culture. The article investigates five Danish adaptations, which compared to Sue’s original serial novel appear as clumsy and uninspired. At the same time the production of popular serial literature is seen as a weighty contribution to the general modernization of the Danish literary culture in the second half of the 19th century.